PREPARATION OF PILE AND DETERMINATION OF TECHNOLOGICAL INDICATORS - Shirinova, Nilufar Israilovna (Educational Research in Universal Sciences, 2023)
In this article, the function of the piling machine is to thin the pith to the required linear density, to cook the product and to wind it into a reel. The braid is thinned in a stretching device, the ends of the fibers that make up it are straightened, flattened and parallelized, and it is stated that a finer braid is formed from it.